Role of Platelet Cytokines in Dengue Virus Infection - Singh, Anamika; Bisht, Piyush; Bhattacharya, Sulagna; Guchhait, Prasenjit (Frontiers in Cellular and Infection Microbiology, 2020)
Platelets are anucleated blood cells derived from bone marrow megakaryocytes and play a crucial role in hemostasis and thrombosis. Platelets contain specialized storage organelles, called alpha-granules, contents of which are rich in cytokines such as C-X-C Motif Chemokine Ligand (CXCL) 1/4/7, (C-C motif) ligand (CCL) 5/3, IL-8 and TGF-β. Activation of platelets lead to degranulation and release of contents into the plasma. Platelet activation is a common event in many viral infections including human immunodeficiency virus (HIV), H1N1 influenza, Hepatitis C virus (HCV), Ebola virus (EBV) and Dengue virus (DENV). The cytokines IL-8, Regulated on Activation, Normal T Expressed and Secreted (RANTES), tumor necrosis factor α (TNF-α), CXCL1/5 and CCL3 released, promote development of a pro-inflammatory state along with the recruitment of other immune cells to the site of infection. Platelets also interact with Monocytes and Neutrophils and facilitate their activation to release different cytokines which further enhances inflammation. Upon activation, platelets also secrete factors such as CXCL4, CCL5 and fibrinopeptides which are critical regulators of replication and propagation of several viruses in the host. Studies suggest that PF4 can both inhibit as well as enhance HIV1 infection. Data from our lab show that PF4 inhibits interferon (IFN) pathway and promotes DENV replication in monocytes in vitro and in patients significantly. Inhibition of PF4 mediated signalling results in increased IFN production and suppressed DENV and JEV replication in monocytes. In this review, we discuss the role of platelets in viral disease progression with a focus on dengue infection.